The Impacts of Public Hospital Autonomization : Evidence from a Quasi-Natural Experiment - Wagstaff, Adam (World Bank, Washington, DC, 2012)
This paper exploits the staggered rollout of Vietnam s hospital autonomization policy to estimate its impacts on several key health sector outcomes including hospital efficiency, use of hospital care, and out-of-pocket spending. The authors use six years of panel data covering all Vietnam s public hospitals, and three stacked cross-sections of household data. Autonomization probably led to more hospital admissions and outpatient department visits, although the effects are not large. It did not, however, affect bed stocks or bed-occupancy rates. Nor did it increase hospital efficiency. Oddly, despite the volume effects and the unchanged cost structure, the analysis does not find any evidence of autonomization leading to higher total costs. It does, however, find some evidence that autonomization led to higher out-of-pocket spending on hospital care, and higher spending per treatment episode; the effects vary in size depending on the data source and hospital type, but some are quite large -- around 20 percent. Autonomy did not apparently affect in-hospital death rates or complications, but in lower-level hospitals it did lead to more intensive style of care, with more lab tests and imaging per case.